Community of inquiry method and language skills acquisition: empirical evidence - Preece, Abdul Shakour Duncan; Bularafa, Mohammed Waziri (2015)
The study investigates the effectiveness of community of inquiry method in preparing students to develop listening and speaking skills in a sample of junior secondary school students in Borno state, Nigeria. A sample of 100 students in standard classes was drawn in one secondary school in Maiduguri metropolis through stratified random sampling technique. A self-developed questionnaire was used in generated the data from the respondents and data was analysed using descriptive consisting of mean and standard deviation as well as and inferential statistics one way ANOVA and multiple regression analysis (MRA).The findings show that speaking skill is stronger than that of listening; gender is significant predictor of speaking skill and no significant difference between students in different classes. The study revealed that community inquiry approach is a good method of teaching speaking skill and teachers should be encourage to master and employ the approach for developing English language skills to students.